Kesalahan-Kesalahan Siswa pada Materi Pecahan - Suparli Suardi; Lukman EL Hakim; Tian Abdul Aziz (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This article aims to analyze articles about student errors in solving problems related to fractions. This article was written using a literature review. The literature used consists of journal articles and books related to the topic of discussion. There are 20 articles to analyze. The articles collected are national articles obtained from Google Scholar, Sinta, and Perpusnas. This article is published in the last 10 years. From the articles collected, the authors summarize all the errors obtained from the results of previous studies, then explain how the error was made and the cause of the error. Based on the literature review, the authors found errors made by students in the fractions theory, including; reading error, understanding error, transformation error, process skill error, error in writing answers (encoding), error in planning problem solving, errors in carrying out problem-solving plans, conceptual error, principle error, random error. The causes of the error, including; lack of student interest in learning mathematics, lack of effort made in working on the given problem, discontinuous way of learning, and lack of mastery of prerequisite theory.